Synthesis of hydrophilic and hydrophobic carbon quantum dots from waste of wine fermentation. Issue 12 (20th December 2017) - Varisco, Massimo; Zufferey, Denis; Ruggi, Albert; Zhang, Yucheng; Erni, Rolf; Mamula, Olimpia
Abstract : Wine lees are one of the main residues formed in vast quantities during the fermentation of wine. While toxic when applied to plants and wetlands, it is a biodegradable material, and several alternatives have been proposed for its valorization as: dietary supplement in animal feed, source for various yeast extracts and bioconversion feedstock. The implementation of stricter environment protection regulations resulted in increasing costs for wineries as their treatment process constitutes an unavoidable and expensive step in wine production. We propose here an alternative method to reduce waste and add value to wine production by exploiting this rich carbon source and use it as a raw material for producing carbon quantum dots (CQDs). A complete synthetic pathway is discussed, comprising the carbonization of the starting material, the screening of the most suitable solvent for the extraction of CQDs from the carbonized mass and their hydrophobic or hydrophilic functionalization. CQDs synthesized with the reported procedure show a bright blue emission ( λ max  = 433 ± 13 nm) when irradiated at 366 nm, which is strongly shifted when the wavelength is increased (e.g. emission at around 515 nm when excited at 460 nm). Yields and luminescent properties of CQDs, obtained with two different methods, namely microwave and ultrasound-based extraction, are discussed and compared. This study shows how easy a residue can be converted into an added-value material, thus not only reducing waste and saving costs for the wine-manufacturing industry but also providing a reliable, affordable and sustainable source for valuable materials.